The Effect of Financial Compensation on Employee Performance : Study Case at Bank SMBC indonesia - Daniel Daniel; Melyani Melyani; Syabrinildi Syabrinildi; Hendra Kurniawan; Fazhar Sumantri; Didin Solehudin; Hendra Lesmana (University of Science and Computer Technology, 2025)
This research investigates the effect of financial compensation on employee performance at Bank SMBC Indonesia. Using a quantitative approach, 120 employees were surveyed via a structured questionnaire. Data were analyzed using SPSS 26, including reliability testing, normality analysis, simple linear regression, ANOVA, and coefficient testing. The results show that financial compensation has a significant and positive effect on employee performance, with an R² of 0.479, meaning that compensation accounts for approximately 47.9% of the variance in performance. Suggestions for SMBC Indonesia include optimizing compensation mechanisms, such as performance-based bonuses, to enhance employee productivity.